Influence of 3D printing parameters on mechanical behaviour of polylactic acid (PLA) specimen utilizing FDM technique - Shathiswara Rao, Subramaniam (2019)
Additive manufacturing is a technology capable to directly manufacture 3D physical model alongside with their inserted mathematical model in an additive nature, where the materials are fused together to form a product, unlike the traditional manufacturing method. The emergence of 3D printing has secured a shorter cycle time for designing and developing innovative products. One of the most common additive manufacturing technologies is Fused deposition modelling (FDM). FDM has been used widely for concept modelling and visualization, fit, form, and functional analysis and rapid manufacturing. The unavailability of extensive printer parameter information which directly reflects the mechanical properties of the 3D printed products has been a barrier for the low-cost 3D printer users to identify the connection between printing parameter, intended application and 3D printer used which becomes the key for reliability and economical factor. Moreover, the potential of a low-cost 3D printer remains blurry since high-end FDM machines are commonly used compared to low-cost FDM machines that just debuted into this business. This research work aims to perform an experimental evaluation on the effects of printing parameter towards the mechanical property of Polylactic Acid (PLA) printed using Fused Deposition Modelling Technique by conducting four types of mechanical tests namely tensile, compression, flexural and impact test. All the specimens were printed according to the requirement stated in ASTM D638, ASTM D695, ASTM D690, and ASTM D256 respectively. Two parameters chosen to be varied in specimen preparation in this research are raster angle and infill density, with value of 0°, 45°, 90°, and 10%, 50%, 99% respectively. Experimental evaluation revealed that all the specimen properties are highly influenced by infill percentage, whereby all the mechanical responses increases with the infill density, making the highest is at 99%. Raster angle showed varied effect with regards to the conducted mechanical test. For tensile properties, ultimate tensile strength and fracture strain were highest at 45° raster angle, while elastic modulus and yield strength were highest at 0° raster angle. Compression properties were not significantly affected by the variation of raster angle. Flexural and impact properties were highest at 0° and 45° raster angle respectively. To validate the experimental data, statistical analysis was carried out using Design of Experiment (DOE) approach with response surface methodology. The average error was calculated comparing experimental and predicted response value, whereby the accountability of obtained experimental data was confirmed with the percentage of error below 10%. Response optimizer was used to maximize the overall mechanical response with regards to the printing parameter combinations. It was determined that the optimum tensile properties were found at parameter combination of 99% infill percentage with 36.36° raster angle. Compression and flexural properties showed an optimum response at 99% infill percentage with 0° raster angle. Finally, impact properties were found to be optimum at 99% infill percentage with 50° raster angle. Experimental evaluation was carried out again to validate the accountability of obtained parameter combinations. This will serve as a guide for 3D printer users to decide on the suitability of low-cost 3D printer to fabricate intended products with needed mechanical property level to comply with the economic factor. As for recommendation, this research work should be extended by including parameters such as printing speed, extrusion temperature, air gap, and layer thickness so that the potential of the low-cost 3D printer can be fully explored.